Assessment of the effect of experimental bleaching agent with nano‐bioactive material on postoperative sensitivity: A randomized, triple blind clinical trial. Issue 5 (23rd June 2021) - Burey, Adrieli; Sutil, Elisama; Nunez Aldaz, Maira Alejandra; Méndez‐Bauer, María Luján; Rezende, Márcia; Reis, Alessandra; Gomes, Osnara Maria Mongruel; Farago, Paulo Vitor; Loguercio, Alessandro D.
Abstract: Objectives: This clinical study aimed to evaluate the effect of incorporating bioactive nanoparticles (n‐Bm) inside an in‐office bleaching gel on the risk and intensity of tooth sensitivity (TS) and on bleaching effectiveness. Materials and methods: Sixty‐six participants were selected and randomly assigned into two groups: control–only in‐office gel and experimental‐in‐office gel with n‐Bm. Teeth were bleached in two sessions (3 × 15‐min). TS was recorded using a VAS and NRS. The color change was evaluated by subjective (VITA Classical and VITA Bleachedguide) and objective (Easyshade spectrophotometer) methods at baseline and 30 days after the end of treatment. The TS was evaluated by McNemar, Wilcoxon Signed Rank, and paired t test. The color changes between groups were compared using paired t test ( α = 0.05). Results: No significant differences between the groups were observed in the risk (control = 27% [95%IC 18–39]; experimental = 21% [95%IC 13–32]) and intensity of TS, as well as in the color change ( p >0.05) for any color measurement. Conclusion: The inclusion of n‐Bm into the bleaching agents did not affect the whitening effectiveness, as well as the risk and intensity of TS between groups. However, the results of the absolute risk of TS were low for both in‐office gels used. Clinical significance: Despite no significant differences between groups, both experimental bleaching agents present suitable results with low values for TS.